POLICING MOBILITY REGIMES frontex and the production of the european borderscape. - Campesi, Giuseppe ([S.l.] : ROUTLEDGE, 2021)
More than 30 years after its birth, the Schengen area of free movement is under siege in Europe: new barriers are being erected along land borders, military assets are increasingly deployed to patrol the Mediterranean, while sophisticated surveillance tools are used tokeep track of the flows of people crossing into European space. Bringing together perspectives from political geography, critical criminology and legal theory, Policing Mobility Regimes offers a systematic analysis of the impact that Frontex is having on migration control strategies at the EU level and offers a detailed empirical description of the agency's organization and operational activities. In addition, this book explores the meaning behind the attempt at developing a post-national border control strategy and what effect this might have on the geopolitics of Europe's borders. It contributes to the wider theoretical debate on the relationshipsamong migration, security and the transformation of borders in contemporary Europe. An accessible and compelling read, this book will appeal to all those engaged with criminology, sociology, geography, politics andlawas well asall those interested in learning about Europe's changing borders.
Keywords: POLITICAL SCIENCE / Political Freedom & Security / Law Enforcement; SOCIAL SCIENCE / Criminology; SOCIAL SCIENCE / Emigration & Immigration; European Border and Coast Guard Agency; Border security -- European Union countries; Freedom of movement -- European Union countries